2002
DOI: 10.1038/ng1065
|View full text |Cite
|
Sign up to set email alerts
|

Birc1e is the gene within the Lgn1 locus associated with resistance to Legionella pneumophila

Abstract: In inbred mouse strains, permissiveness to intracellular replication of Legionella pneumophila is controlled by a single locus (Lgn1), which maps to a region within distal Chromosome 13 that contains multiple copies of the gene baculoviral IAP repeat-containing 1 (Birc1, also called Naip; refs. 1-3). Genomic BAC clones from the critical interval were transferred into transgenic mice to functionally complement the Lgn1-associated susceptibility of A/J mice to L. pneumophila. Here we report that two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
205
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(214 citation statements)
references
References 29 publications
5
205
0
4
Order By: Relevance
“…The protein encoded by the BIRC1 gene contains regions of homology to two baculovirus inhibitors of apoptosis, and suppresses apoptosis induced by various signals. 62,63 As CML is characterized by increased resistance to apoptosis, this result may seem contradictory to the pathophysiology of CML. However, apoptosis regulation is mediated by a number of different effectors, and the balance between multiple pro-and antiapoptotic genes decides the fate of the cell, rather than expression of one single gene product.…”
Section: Discussionmentioning
confidence: 63%
“…The protein encoded by the BIRC1 gene contains regions of homology to two baculovirus inhibitors of apoptosis, and suppresses apoptosis induced by various signals. 62,63 As CML is characterized by increased resistance to apoptosis, this result may seem contradictory to the pathophysiology of CML. However, apoptosis regulation is mediated by a number of different effectors, and the balance between multiple pro-and antiapoptotic genes decides the fate of the cell, rather than expression of one single gene product.…”
Section: Discussionmentioning
confidence: 63%
“…19 NAIP was the first mammalian IAP to be discovered, but rather than having a role in regulation of cell death, it is a 44,45 that appears to function in providing innate immunity to infection by bacteria such as Leigonella pneumophila. 46,47 Although some initial reports suggested it might be able to inhibit caspases in vitro, subsequent studies have shown NAIP cannot directly inhibit caspases at physiological concentrations. 29 Similarly, although Survivin, an IAP that acts together with aurora kinase B and the inner centromere protein during mitosis, was initially proposed to inhibit caspases, 48 it is no longer thought to be able to do so.…”
Section: Iapsmentioning
confidence: 99%
“…Nalp3 activates caspase 1 via a pyrin domain, but does so by using the adaptor protein ASC to recruit caspase 1 (3). The NLR Naip5 was identified as the Legionella pneumophila susceptibility locus in A/J mice (6,7). Because Ipaf also provides resistance to L. pneumophila infection and Ipaf and Naip5 have been shown to interact with each other in overexpression assays, it has been suggested that the two work in concert to activate caspase 1 (8)(9)(10)(11).…”
mentioning
confidence: 99%